Blocking the transmission of heartworm (Dirofilaria immitis) to mosquitoes (Aedes aegypti) by weekly exposure for one month to microfilaremic dogs treated once topically with dinotefuran-permethrin-pyriproxyfen - McCall, John W. (Parasit Vectors, 2017)
BACKGROUND: This study assessed the influence of a topical ectoparasiticide (dinotefuran-permethrin-pyriproxyfen, DPP, Vectra®3D, Ceva Animal Health) on the acquisition of heartworm microfilariae by mosquitoes exposed to microfilaremic dogs weekly for 1 month. METHODS: Six beagle dogs (9.2 ± 1.6 kg body weight) infected with Dirofilaria immitis were allocated to two groups of three dogs: an untreated control group and a DPP-treated group. Dogs were treated on Day 0 and exposed under sedation for 1 h to 80 ± 20 unfed Aedes aegypti. Each dog was exposed to mosquitoes released into mosquito-proof containers on Days −7 (pretreatment), 7, 14, 21 and 28. Up to 20 engorged mosquitoes were aspirated from the cage as soon as they were blood-fed. They were dissected and the blood from each midgut was stained for a microfilaria (MF) count. After each exposure, mosquitoes were classified as live, moribund or dead and engorged or nonengorged. The number of dead mosquitoes was recorded daily for 16 days, when the live mosquitoes were dissected to count the infective third-stage larvae (L3). RESULTS: Prior to treatment, 95% of the engorged mosquitoes in both groups had MF. After treatment, engorgement rates for the treated group were 0%, 2.3%, 2.7% and 2.2% for Days 7, 14, 21 and 28, respectively, with anti-feeding efficacy (repellency) of 100%, 98.0%, 95.8% and 97.0%, respectively. A total of 22 mosquitoes fed on treated dogs; most of them were dead within 24 h, and all were dead within 72 h. Only 2 unfed mosquitoes exposed to treated dogs survived the incubation period and no L3 were found in them. A total of 121 of the 132 (91.6%) surviving mosquitoes that had engorged on untreated dogs had an average of 12.3 L3 per mosquito (range, 0-39). CONCLUSIONS: DPP was more than 95% effective in inhibiting blood-feeding and killing both engorged and nonengorged mosquitoes exposed weekly to microfilaremic dogs for 28 days after treatment. Treatment with DPP was completely effective in killing the few mosquitoes that fed on the treated dogs before they lived long enough for the microfilariae to develop to L3 and, consequently, was completely effective in blocking the transmission of L3 to other animals. DPP can break the life cycle of D. immitis and prevent infected dogs and infected mosquitoes from being effective reservoirs and can slow down the spread of heartworms, even those resistant to macrocyclic lactone preventives.